Etnoecologia da pesca artesanal e percepção ambiental sobre os impactos à ictiofauna no submédio e baixo São Francisco - Sousa, Thiago D’Avilla Gomes de (2018)
Studies with traditional communities have demonstrated the important artisanal fishermen knowledge about the ecological and behavioral aspects of fishes, representing a precise source of local knowledge constituted under acquisition, practice and transmission between generations. The present study had as objective to obtain data on the Local Ecological Knowledge of artisanal fishermen about the environmental impacts to the ichthyofauna of sub-middle and lower São Francisco river basin, as well as information that indicates the possible status of occurrence of the species. Expeditions for data collection were carried out in four areas totalizing 75 field days between March and August 2017. A total of 107 fishermen from 22 localities of the states of Bahia, Pernambuco, Sergipe and Alagoas were selected through snowball method, and participated in the study through methods of free, semistructured interviews, visual stimuli and guided tour. It was reported that important migratory species were extinct locally, such as Pirá Conorhynchus conirostris (+20 years), Surubim Pseudoplatystoma corruscans and Dourado Salminus franciscanus (+10 years), as well as the reduction of the Mandi species in AREA 1 and its probable extinction downstream from Xingó. Species such as Piau-cutia Megaleporinus obtusidens and the Curimatás Prochilodus argenteus and P. costatus were mentioned as rare due to the scarcity of catching in the last decade. Rheophilic species such as Piau-preto Leporinus piau and Piau-manteiga Leporinus reinhardti currently play an important role in the local economy, maintaining viable populations possibly due to the existence of small tributaries in the region. There was an increase in resident species as well as non-native species, such as Apaiari Astronotus ocellatus, Pacu-CD Metynnis lippincottianus, Tucunaré Cichla monoculus, Tilapia Oreochromis niloticus and Pescada Plagioscion squamosissimus (restricted to AREA 1), which benefited from modifications to its establishment. Results from the present study were corroborated, evidencing the importance of using the CEL of fishermen in the decisionmaking processes. The change in the structure of the ichthyofauna was mainly related to the dams (93%), as well as the presence of macrophytes (27%), pollution (21%), overfishing (18%), drought (17%), aquaculture (15%) and deforestation (12%). The Similitude analysis demonstrated a high expression of the impacts caused by dams, as well as their association with non-native species and silting. The multivariate analysis of Non-Metric Multidimensional Scaling (NMDS) and Dissimilarity (ANOSIM) showed a significant difference (p <0.001) in the manifestation of impacts in AREA 1 in relation to the others, since the area is under direct influence of the largest number of São Francisco River dams and strong pressure of the commercial production of O. niloticus in fish farm. The salinization was evidenced in AREA 4, which has contributed to the advance of marine species and intensified the losses related to the fishery. All of these impacts have triggered numerous socioeconomic problems for fishing communities that have artisanal fishing as their main source of subsistence. Fishermen also made suggestions for the conservation of fishing resources and the São Francisco river. The problematic needs the urgent attention from public authorities and related entities so that effective measures are taken to mitigate impacts to the native fish fauna of the São Francisco river.